Investigation of typhlitis in bone marrow transplant patients in a stem cell transplant unit - TOPTAŞ, TAYFUR (My University, 2022)
Typhlitis is a special type of enterocolitis that specifically develops in immunosuppressive patients with hematological malignancies. Typhlitis is a common consideration after bone marrow transplantation due to high-dose chemotherapy that is used in conditioning regimens those contain high-dose cytotoxic chemotherapeutic agents. Although there are several studies about typhlitis during chemotherapy or in leukemia patients, there is not enough data evaluating its relationship between stem cell transplant in adults. Therefore, the current study aimed to analyze the possible causes that may lead to the development of typhlitis in hematopoietic stem cell recipient patients. This retrospective study included 210 adult patients who underwent bone marrow transplantation between January 2017 and December 2019. Pediatric patients (patients younger than 18 years of age) were excluded. Patients\" data were evaluated to determine their effects on typhlitis and the mortality risk of the patients with typhlitis. The analysis of the variables was performed using the IBM SPSS Statistics for Windows version 26 (IBM Corp., Armonk, NY).Variables were analyzed at a 95% confidence level and a P value <0.05 was considered significant. Typhlitis developed in 23 (10.9%) transplant patients. Male sex, length of hospital stay, presence of febrile neutropenia, antibiotic and antifungal use, need for switching antibiotics, duration of neutropenia, diarrhea and antibiotic use in days were risk factors for development of typhlitis. It was observed that 100-days mortality was higher in typhlitis group reaching to a statistical significance (P < .05). In multiple logistic regression analysis, presence of mucositis and additional source of infection were determined as independent risk factors for the development of typhlitis in bone marrow transplant patients. This study provides valuable information for bone marrow transplant patients through an analysis of risk factors for the development of typhlitis. According to our results, mucositis and additional bacterial infections were found as risk factors for typhlitis therefore it would be beneficial for clinicians to consider these factors in patient follow-up. However, due to the retrospective nature of our study, prospective studies are needed to investigate risk factors and optimum treatment methods for typhlitis.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & İÇECEK; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine